Vesicular structures formed from barley wort proteins and iso-humulone. (August 2020) - Lu, Yi; Osmark, Peter; Bergenståhl, Björn; Nilsson, Lars
Abstract: In beer, the main amphiphilic components are protein and iso-humulone. Two major populations of protein are identified as lipid transfer protein (LTP) (9.7 kDa) and protein Z (43 kDa). In this paper, protein and iso-humulone are extracted from barley malt and hop, respectively, based on the brewing process. Mixtures of protein and iso-humulone are mixed at different concentrations and centrifuged. Supernatants are analyzed by asymmetric flow field-flow fractionation (AF4) coupled to UV with multi-angle light scattering (MALS) detection as well as by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE). The presence of aggregates and their structures are investigated by light microscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results show that protein and iso-humulone can form aggregates from molecular level by AF4-UV-MALS and SDS-PAGE. The interaction is shown as solution depletion which is analyzed by AF4-UV-MALS. With 300 mg/L iso-humulone and 3 g/L protein in bulk, the decrease of protein peak levels off. The peak of protein Z is preferentially decreased as an effect of iso-humulone being present, suggesting that interaction between these populations is favored. The iso-humulone/protein aggregates consist of both undefined irregular aggregates as well as spherical aggregates. The spherical aggregates are observed in light microscopy, SEM and TEM. From SEM, it is clear that there are two types of spherical aggregates: rough and smooth. With TEM it can be observed that the smooth aggregates consist of a thin layer of the aggregated proteins and iso-humulone enclosing a liquid domain. This structure can best be described as an iso-humulone/protein vesicle. The rough vesicles are formed by further precipitation at the surface of the smooth vesicles. Graphical abstract: Image 1 Highlights: Iso-humulone aggregates mainly with protein Z, and less with LTP. Aggregates are large uncharacteristic floccs, but also vesicules Vesicular aggregates are spontaneously formed in 1–20 μm.